FANCD2 Western blot as a diagnostic tool for Brazilian patients with Fanconi anemia - D.V. Pilonetto (Brazilian Journal of Medical and Biological Research, 2009)
Fanconi anemia is a rare hereditary disease showing genetic heterogeneity due to a variety of mutations in genes involved in DNA repair pathways, which may lead to different clinical manifestations. Phenotypic variability makes diagnosis difficult based only on clinical manifestations, therefore laboratory tests are necessary. New advances in molecular pathogenesis of this disease led researchers to develop a diagnostic test based on Western blot for FANCD2. The objective of the present study was to determine the efficacy of this method for the diagnosis of 84 Brazilian patients with Fanconi anemia, all of whom tested positive for the diepoxybutane test, and 98 healthy controls. The FANCD2 monoubiquitinated isoform (FANCDS+/FANCD2L-) was not detected in 77 patients (91.7%). In 2 patients (2.4%), there was an absence of both the monoubiquitinated and the non-ubiquitinated proteins (FANCD2S-/FANCD2L-) and 5 patients (5.9%) had both isoforms (FANCD2S+/FANCD2L+). This last phenotype suggests downstream subtypes or mosaicism. All controls were diepoxybutane negative and were also negative on the FANCD2 Western blot. The Western blot for FANCD2 presented a sensitivity of 94% (79/84) and specificity of 100% (98/98). This method was confirmed as an efficient approach to screen Brazilian patients with deleterious mutations on FANCD2 (FANCD2S-/FANCD2L-) or other upstream genes of the FA/BRCA pathway (FANCDS+/FANCD2L-), to confirm the chromosome breakage test and to classify patients according to the level of FA/BRCA pathway defects. However, patients showing both FANCD2 isoforms (FANCD2S+/FANCD2L+) require additional studies to confirm mutations on downstream Fanconi anemia genes or the presence of mosaicism.